COVID-19 and Prophylactic Measures for HIV Children of Ratodero, Larkana - Irshad Hussain ,Muhammad Shehzad Raza ,Saleem Ahmed Joyo (Journal of Rawalpindi Medical College, 2020)
Ratodero is Taluka of population 224,000 in the district Larkana of Sindh, Pakistan. In the HIV outbreak (2019), 1132 HIV patients were reported in the Ratodero, amongst them, 901 (80%) were children, and the majority (735) below the age of 5 years.1 Larkana district is included among the cities where eight (8) COVID-19 carrier pilgrims from Iran were first confirmed as virus positive.2 Followed by community transmission in the area with the confirmation of the virus in the two individuals.3 There was reported shortage of the personnel protection equipment (PPEs) for the Medical Professional engaged in the tests of the COVID-19 as well as the shortage of Kits, so less number of COVID-19 tests were conducted, therefore the actual number of COVID-19 positive can abruptly raise with the availability of Kits and PPEs.4 There is a complete lockdown in the area since last week of March 2020. There is one medical University with an affiliated hospital. Collaborative efforts of the University teaching hospital and the district administration have constituted a team of experts for necessary actions to combat with expected Corona-19 outbreak. In such circumstances of the existence of HIV in Ratodero as an alarm of threats for another health risk for the poor HIV children of Ratodero Larkana. Dated 09 April 2020. there was a random selection of 20 such HIV children of Ratodero below the age 5, to have look on their physical health and to confirm the quantity/availability of ART (antiretroviral treatment) at their home. It was found that 30% of children were found physically weak. The confirmed average availability of remaining ART drugs was found available for use in the next 14 days. Generally, the children are the population of developing immunity (vulnerable age group) hence there can be increased risk if Co-Infection of COVID-19 if hits the Ratodero Taluika. Therefore the District of Larkana in general but the Taluka Ratodero, in particular, need special attention from the health administration. Following preventive measures can be useful to prevent the spread of COVID-19 among the HIV children of Ratodero, Larkana. Better compliance of prophylactic SOPs verses COVID-19 through proper surveillance at the rural level in Ratodero. Availability of Rashan on priority for the families of registered HIV children of Ratodero, taking into account the inclusion of all requirements of good nutrients in the daily intake. COVID-19 screening of registered HIV children. HIV Screening of any COVID-19 career of Ratodero if the individual is not amongst already registered HIV patients. Establishment of a dedicated isolation ward in case of Co-Infection in these children along with the provision of special care to prevent the onset of COVID-19 symptoms in these patients. Advance Supply of 03 to 06 month ART at home as per instructions of the World Health Organization (WHO) for such HIV patients.5